External Pelvimetry of Cattle and Buffaloes and its Association with the Incidence of Dystocia - Kafle, Ashesh; Gautam, Gokarna; Poudel, Amrit; Kandel, Bishal (Journal of Agriculture and Forestry University, 2026)
Pelvimetry is the measurement of dimensions of bony pelvis for the assessment of pelvic area. The objectives of this study were to determine the pelvic dimensions of cross-bred cattle and buffaloes using non-invasive external pelvimetry and to understand the association of pelvic dimension with the incidence of dystocia. Total 111 cows and 58 buffaloes were included in the study. Distances between two hook bones, two pin bones and that from top of the croup to the level of hip joint were measured using a measuring tape and scale; the established formulas were used to determine the transverse and conjugate diameters, mean diameter and area of the pelvic inlet. Body weight was estimated using a Shaeffer’s formula by measuring heart girth and body length. Conjugate diameter and pelvic area to body weight ratio (PA:BW) were found to be significantly lower in dystocic animals than in non-dystocic ones. Pelvic area was additional significant parameter in dystocic buffaloes. Conjugate diameter was significantly associated with higher odds of dystocia. There was a tendency that male calves had 6.23 times greater odds of causing dystocia than female calves. This study documented pelvimetric data and its association with dystocia in cross-bred cattle and buffalo in Nepal, which could be an important selection criteria in breeding programs.